Galectin-3 orchestrates the histology of mesentery and protects liver during lupus-like syndrome induced by pristane - Lemos, F. S. (Sci Rep, 2019)
Galectin-3 (Gal-3) controls intercellular and cell-extracellular matrix interactions during immunological responses. In chronic inflammation, Gal-3 is associated with fibrotic events, regulates B cell differentiation and delays lupus progression. Gal-3 deficient mice (Lgals3(−/−)) have intense germinal center formation and atypical plasma cell generation correlated to high levels IgG, IgE, and IgA. Here, we used pristane (2,6,10,14-tetramethylpentadecane) to induce lupus-like syndrome in Lgals3(−/−) and Lgals3(+/+) BALB/c mice. Mesentery and peritoneal cells were monitored because promptly react to pristane injected in the peritoneal cavity. For the first time, mesenteric tissues have been associated to the pathogenesis of experimental lupus-like syndrome. In Lgals3(+/+) pristane-induced mice, mesentery was hallmarked by intense fibrogranulomatous reaction restricted to submesothelial regions and organized niches containing macrophages and B lymphocytes and plasma cells. In contrast, Lgals3(−/−) pristane-treated mice had diffuse mesenteric fibrosis affecting submesothelium and peripheral tissues, atypical M1/M2 macrophage polarization and significant DLL1(+) cells expansion, suggesting possible involvement of Notch/Delta pathways in the disease. Early inflammatory reaction to pristane was characterized by significant disturbances on monocyte recruitment, macrophage differentiation and dendritic cell (DC) responses in the peritoneal cavity of pristane-induced Lgals3(−/−) mice. A correlative analysis showed that mesenteric damages in the absence of Gal-3 were directly associated with severe portal inflammation and hepatitis. In conclusion, it has suggested that Gal-3 orchestrates histological organization in the mesentery and prevents lupoid hepatitis in experimental lupus-like syndrome by controlling macrophage polarization, Notch signaling pathways and DC differentiation in mesenteric structures.